Community re-education on the urgency of keeping the river clean and sorting waste in Desa Cikole Kec. Lembang - Rachmat Ichwan Nurdin; Hafsah Nugraha; Isye Iswari Arbie; Salma Almira Hamdani; Rizza Lestari; Ilvira Khoerunnisa; Rima Rachmawati; Tina Aprilia; Muhammad Vidia Adhiyaksa; Romi Samsuhardo; Billy Idan Setiadi; Mupid Hidayat (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Lembang area is one of the contributors to water pollution in the Cibeureum and Cikapundung rivers which empties into the Citarum river. One of the things that pollute it is animal waste because some residents habitually throw it directly into the river. The program's dedication in the form of Kuliah Kerja Nyata (KKN), published in this article, aims to increase the awareness of residents and students about the importance of sorting and processing waste. Also, providing education that maintaining cleanliness in Cikole has helped reduce the problem of the Citarum river. It includes education about composting as a way to process animal manure. The method used is value planting and a synergy approach. Some of the programs carried out are the Harum Citarum Seminar by the TNI SATGAS, river carcasses, composting, making organic, inorganic, and B3 trash cans, social services or cooperation, and the commemoration of the Republic of Indonesia's anniversary. After implementing the program, most residents and school students realized the importance of protecting the environment, as seen by the amount of waste disposed of carelessly in several areas. The community has also understood the importance of keeping the environment clean, especially around the river.